Model Integrasi Ilmu Pada Silabus Mata Kuliah Psikologi Kepribadian - Wahyudi, Imam; Husaini, Adian; Hafidhuddin, Didin; Suryadi, Bambang (Ta'dibuna: Jurnal Pendidikan Islam, 2017)
This study aims to determine: (1) What personality psychology syllabus content Islami (2) how the depth of the material being taught personality psychology, and (3) how the competencies of personality psychology lecturer Islami (4) how the integration model of personality psychology West and Islam. The research is a qualitative research, carried out at two Islamic universities namely Lampung Muhammadiyah University and the State Islamic Institute Raden Intan Lampung. Capturing data source is purposive and snowbaal, data analysis is inductive/qualitative. Data collection through interviews, observation, documentation. Analysis and interpretation of data from data reduction, data display verification and draw conclusions. The result of this study indicate that two Islamic Universities in Lampung ie the Psychology Program of Muhammadiyah’s Lampung University and Islamic Psycology Program of IAIN Raden Intan Lampung, still taught their students the psychology of personality in the perspective of western view. The worldview of lecturers in teaching has not been using an integrated approach to interconnect. Efforts to integrate the science of personality psychology begins with the conceptual mastery includes axiology, epistemology and ontology. Axiology psychology Islamic personality that is based on the source of Islamic law revelation (al-Qur'an and as-sunna). Islamic personality psychology is the scientific study that seeks to understand the circumstances and causes of individual behavior by source of truth to the holy book. Epistemology of personality psychology Islam is the way to seek the truth about the substance that is to be disclosed, epistemology talk about what can be known and how to find out. In this issue, meaning aksiologik was instrumental in determining the truth epistemologik. Ontology function sets the substance to be achieved is to understand human beings in accordance with sunnatullahnya. Then verses that talk about including the terms as nafs, man, basyar, aql, soul, qalb can be used as a reference. To be able to pursue the meaning and essence, not just the symptoms. There are five stages in the development of curriculum (syllabus) Islamic personality psychology courses (integrated): first do the analysis, the design, development third, fourth fifth and final implementation evaluation. Starting from the early stages of preparing the course syllabus integrated personality psychology known ADDIE development model. The integration model of Western and Islamic Psychology is implemented at various levels, namely: (1) Philosophy level, (2) material level which done in three models, the first, the integration in the curriculum. The second, naming model in the field that shows the relationship between Islamic and other field. The third, the integration model in doing the learning process. (3) reviewing the concepts and theories of western psychology by sorting out the contents that contradict the teaching of Islam. (4) Strategy level. In this level, the lecturers’ quality and skill were as the key of success in running learning based on interconnect integration. Keyworld: Integration model, islamic psychology, personality